Native silver in the eastern part of the Karkonosze granitoid pluton, Lower Silesia, Poland - Kozłowski, Andrzej; Matyszczak, Witold (Acta Geologica Polonica, 2023)
This article describes silver specimens of the size of tenths to a few millimetres, found in small pegmatites and quartz veinlets of the porphyritic granitoid area in 22 sites in the eastern part of the Variscan granitoid Karkonosze pluton, from 20 of which native silver occurrences were previously not known. The sites are scattered on the whole surface of the granitoid. The native silver occurred in wire, rod, platy, dendritic, anhedral granular and euhedral cubic and octahedral habits; in some specimens twins and fenster faces were also found. Associated with native silver small amounts of acanthite crystallized commonly, sometimes apparently formed by sulphur diffusion into silver. Inclusions of native gold, electrum, galena, chalcopyrite and pyrite occurred in the native silver. The parent fluids of the specimens were epithermal, because the homogenization temperature (Th) of inclusions in quartz, calcite and cleavelandite that were the host minerals of the native silver was generally 91–165ºC and for individual samples the Th range was 4–11ºC. The total salinity of the fluid was 2.4–7.2 wt. % with Na and Ca (hydro)carbonates as the main dissolved components and admixtures of K, Mg, Fe, Al, S, Cl and F. The parent granitoid contains Ag in trace amounts (0.034–0.056 ppm) and was probably the source of this element for the crystals of native silver. Migration of Ag was made easier by the presence of fluoride ions in fluids.
Keywords: Native silver; Fluid inclusions; Granitoid; Karkonosze pluton